PENGARUH PENERAPAN PENDEKATAN RECIPROCAL TEACHING DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI SMKN 1 KOTO BARU KABUPATEN DHARMASRAYA - Novianti, Deti; Rismen, Sefna; Haryono, Yulia (Pendidikan Matematika, 2013)
This research is motivated by the students comprehension of mathematical concepts in learning is low. This research aims to determine: 1) how the development of students comprehension of mathematical concepts using Reciprocal Teaching approach in learning mathematics with Quiz experimental class students in class XI SMKN 1Â  Koto Baru Kabupaten Dharmasraya and; 2) whether students comprehension of mathematical concepts by applying the Reciprocal Teaching approach with better Quiz comprehension of the mathematical concept of students with learning conventional in class XI SMKN 1 Koto Baru Kabupaten Dharmasraya. The research was an experiment with random design subject. The population in this research is the class XI students enrolled in the school year 2012/2013. Sampling technique is random. The instrument used in this research are quiz and final test in the form of essays. Technical analysis of the data used is the t because two samples are normally distributed and the data are not homogeneous. T test results obtained thitung = 3.17 and ttabel = 1.713 at Î± = 0.05, thitung> ttabel, it can be concluded that the students comprehension of mathematical concepts using Reciprocal Teaching approach accompanied Quiz better than conventional learning at SMKN XI 1 Koto Baru Kabupaten Dharmasraya.